2012
DOI: 10.1021/la2050866
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the Interface between Glucose Oxidase and Nanoparticles

Abstract: The behavior of glucose oxidase (GOx) on gold nanoparticles (NPs) was investigated as a function of (1) NP surface chemistry, (2) stabilizing protein additives, and (3) protein microenvironment. GOx secondary structure and unfolding was probed by circular dichroism (CD) spectroscopy and fluorescence, and GOx enzymatic activity was measured by a colorimetric assay. We also examined the activity and structure of GOx after displacement from the NP surface. Generally, GOx behavior was negatively impacted by conjug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 51 publications
4
40
0
Order By: Relevance
“…3b features two minima at 218 and 208 nm and a maximum at 193 nm. This spectrum is close to that of native GOx, which adopts predominantly an α-helical structure that leads to two negative bands at 222 and 208 nm and a positive band at 193 nm [44]. For immobilized GOx in the rGO-containing LbL film the CD spectrum displays two negative bands at 220 and 210 nm and a positive band at 193 nm.…”
Section: Characterization Of Gpss and Gpddasupporting
confidence: 58%
“…3b features two minima at 218 and 208 nm and a maximum at 193 nm. This spectrum is close to that of native GOx, which adopts predominantly an α-helical structure that leads to two negative bands at 222 and 208 nm and a positive band at 193 nm [44]. For immobilized GOx in the rGO-containing LbL film the CD spectrum displays two negative bands at 220 and 210 nm and a positive band at 193 nm.…”
Section: Characterization Of Gpss and Gpddasupporting
confidence: 58%
“…However, DET between GOx or GDH and electrode surface can be very slow due to the protein shell shielding the enzyme active site (Bankar et al, 2009). The efficiency of DET depends not only on the distance between the active site of the enzyme and the electrode but also on the properties of the electrode material and on the immobilization technique (Tellechea et al, 2012, Ludwig et al, 2013). For the limited number of GOx and GDH that are capable of DET, the efficient electron transfer still requires conformational change of the enzyme, which may result in an obvious loss of activity (Felice et al, 2013, Seehuber and Dahint, 2013).…”
Section: The Development Of Glucose Metermentioning
confidence: 99%
“…1(c) and (d)). Likewise, Hamad-Schifferli et al reported that irreversible denaturation of Glucose Oxidase (GOx) caused by the interaction with NPs had a negative effect on its enzymatic activity [33]. Recently, Das et al reported that NPs can also improve enzymatic activity [34].…”
Section: Modulating the Interaction Between Nps And Biological Systemsmentioning
confidence: 99%